Predictive analytics for business (International Journal of Food and Nutritional Sciences, 2022)
This paper offers a complete examination of predictive analytics in the business panorama. Itexplores essential concepts, methodologies, and applications, focusing on gadget getting toknow algorithms, statistical models, and facts integration.